Advances in immunotherapy for uveal melanoma: enhancing efficacy and overcoming resistance - Song, Jian; Mou, Pei; Song, Guo-Ge; Chen, Liang; Chen, Yu-Qing; Wei, Rui-Li (Frontiers in Cell and Developmental Biology, 2025)
Uveal melanoma (UM) is the most common primary intraocular malignancy in adults, presenting a significant clinical challenge due to its high metastatic potential and limited response to conventional systemic therapies. While immunotherapy has transformed the treatment landscape for numerous cancers, its effectiveness in UM has been substantially limited, primarily due to the tumor’s distinct immune-evasive characteristics and a suppressive tumor microenvironment (TME). This review systematically examines the multiple mechanisms underlying immunotherapy resistance in UM, including low tumor mutational burden, immune checkpoint overexpression, metabolic adaptations, and the epigenetic silencing of immune-stimulatory genes. Additionally, we analyze emerging strategies aimed at modifying the TME to enhance immune recognition and response, which include targeting suppressive immune cell populations, addressing metabolic and hypoxic barriers, and utilizing epigenetic modulators to restore immune activation pathways. Furthermore, we highlight recent advances in identifying predictive biomarkers—such as genetic mutations (e.g., BAP1, MBD4), immune gene signatures, circulating tumor DNA, and protein-based blood markers—that may facilitate patient stratification and treatment selection. We also examine novel combination approaches that integrate immune checkpoint inhibitors with targeted therapies, radiation, metabolic interventions, or engineered cellular therapies, several of which have shown promising clinical potential in overcoming UM’s inherent resistance mechanisms. Despite persistent challenges, such as toxicity management and limited availability of large-scale trials due to UM’s rarity, the integration of multi-omics profiling, precision medicine frameworks, and adaptive trial designs presents new opportunities for therapeutic advancement. This review provides a translational perspective on enhancing immunotherapy efficacy in UM by addressing its unique biology and identifying future directions for clinical innovation.